Thresholds for cavitation produced in water by pulsed ultrasound - Atchley, A; Frizzell, L; Apfel, R; Holland, C; Madanshetty, S; Roy, R (Elsevier, 1988)
The threshold for transient cavitation produced in water by pulsed ultrasound was measured as a function of pulse duration and pulse repetition frequency at both 0.98 and 2.30 MHz. The cavitation events were detected with a passive acoustic technique which relies upon the scattering of the irradiation field by the bubble clouds associated with the events. The results indicate that the threshold is independent of pulse duration and acoustic frequency for pulses longer than approximately 10 acoustic cycles. The threshold increases for shorter pulses. The cavitation events are likely to be associated with bubble clouds rather than single bubbles.